Lost opportunities: Market work during high school, establishment closures and the impact on career prospects - Dagmar Müller (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
In this paper, I study the importance of market work during high school for graduates' school-towork transition and career prospects. Relying on Swedish linked employer-employee data over a 30-year period, I show that market work during school provides students with an important job search channel, accounting for 30 percent of direct transitions into regular employment. I use the fact that some graduates are deprived of this channel due to establishment closures just prior to graduation and labor market entry. I compare classmates from vocational tracks with the same field of specialization to identify the effects of the closures and show that lost job-finding opportunities due to an establishment closure lead to an immediate and sizable negative effect on employment after graduation. The lost employer connection have also persistent, but diminishing negative effects on employment and earnings for up to 10 years, but are not permanent. Parts of the effect appear to be driven by a process where graduates who are subject to a closure of a relevant employer before graduation have to find employment in an industry which is less relevant to their education.
Keywords: J01; 330; social contacts; young workers